PROSPECTS AND CHALLENGES FOR FUTURE ISLAMIC RELIGIOUS EDUCATION TEACHERS - Millatina, Nurma; Azfar, Fani (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
This article discusses the prospects and challenges that Islamic religious education teachers must face in the future. In this XXI century, the world has echoed the development of IT as a result of the emergence of the industrial revolution 4.0 and society 5.0 which brings various sophistication of scientific and technological advances. This study focuses on two main points, namely first, the prospect of Islamic religious education teachers in the future and second, the challenges of Islamic religious education teachers in the future. This study uses library research method with content analysis approach. The results of this study found that the development of the times both era 4.0 and era 5.0 is not something that needs to be feared and avoided by Islamic education teachers, it must be faced with a wise and optimistic attitude. The progress of era 4.0 and 5.0 both contain various prospects and challenges for PAI teachers. As a form of response, PAI teachers should prepare themselves with various competencies so that they can still exist as true educators who can inspire their students for the achievement of educational goals. PAI teachers should view the upcoming prospects as a golden opportunity in improving the quality of Islamic education comprehensively and the upcoming challenges as a motivation to measure and develop their potential.